MARKET TRENDS IN THE DEVELOPMENT OF COMPANIES IN THE SPHERE OF INTELLECTUAL BUSINESS SERVICES - S. Ponomareva (Вестник университета)
This article investigates the development of companies in the sphere of intellectual business services in the face of changing market trends of their development. The author defines the main features of the market of intellectual business services, illustrating their matrix factor in the success of sales of intelligent business services, determines the causes of the low price elasticity of the consulting markets. Focusing on the growth prospects of the market of intellectual business services management and shareholders of companies in this sphere, as well as potential investors with each passing years will show an increased interest in the development prospects of this business, which will lead to growing needs of management companies to develop not only short-term forecasts of growth in the value of the business, but actualizes the need to develop financial strategies that turn will put forward higher requirements for the information of financial statements and budgets of companies in the sphere of intellectual business services.